Emerging intervention of antidepressant with DMARD in non-cancerous nociceptive persistent pain associated depression in FCA induced rheumatoid arthritic rats - Sudhakar Pachiappan; Sudaroli Murugaiyan; Sabarinath Chandrasekar (Universidade de São Paulo, 2021)
Rheumatoid arthritis (RA) is a chronic inflammatory disorder that causes pain, systemic complications and premature mortality. Depression has also been identified as a problem for persons with RA. This association remaining significant even after the degree of disease activity is controlled. In the present study, the efficacy of combination therapeutic effect of antidepressant (amitriptyline) with Disease Modifying Anti rheumatoid drug (leflunomide) was determined in rheumatoid arthritis pain associated depression in Freund's complete adjuvant (FCA) induced arthritic rats. Drug treatment was started 9 days after induction of FCA induced arthritis in rats. The antiarthritic activity was assessed by measuring paw volume, weight-bearing, hematological, biochemical, serological parameters, Radiographic analysis and Histopathology of tibiotarsal joints. The antidepressant activity was assessed by Forced swimming test, Rota-rod test and confirmed by estimation of brain neuro transmitters (serotonin and norepinephrine) level. Results of this study revealed that leflunomide and amitriptyline combination showed more significant (p<0.001) antiarthritic and antidepressant action and leflunomide alone treatment showed significant (p<0.001) antiarthritic activity only as compared to arthritic control. The leflunomide and low dose amitriptyline combination found to be more effective in pain associated depression in rheumatoid arthritic rats.